Expression of pathogenesis-related proteins in potato brown rot plants confers resistance to filamentous pathogens under field trials - Hanaa S. Omar; Mohamed H. Hagag; Dina El-Khishin; Mona Hashem (Scientific Reports)
Abstract The present investigation aims to use innovative metagenomics technologies and denaturing gradient gel electrophoresis (DGGE) to compare the microbial communities of conductive and suppressive soils in connection to brown rot disease in the entire value of Egyptian potato imports. Besides evolution, the bioefficacy of two biocontrol agents, either alone or in consortium, on plant growth promotion and activation of defense responses in potato against the brown rot diseases. The soil status of collecting soil from seven different locations in different governorates was evaluated for tolerance to the artificial inoculation of the pathogen agent of R. solanacearum on potato plants. The DGGE uses 16 srRNA primers that were used to compare two extreme patterns for identifying the microbial population detected in environmental samples. Different bands were extracted from the DGGE gel and sequenced. The sequencing data results revealed that the biocontrol agent factor has a 100% gene bank similarity and belongs to the Pseudomonas species. The Pseudomonas nucleotide sequences isolates were deposited in the Gene Bank under Accession Nos. PP930812, PQ466864, and PQ470140. The findings showed that the soil from the governorates of Kerdasa exhibited a less tolerant treatment, with an estimated disease severity of 78.33%. On the other hand, ElBeheira Kom Hamada soil showed significant tolerance, with an estimated disease severity of 11.67. According to the data of gene expression analysis, both treated plants with the biocontrol agents showed a significant increase in PR-1, PR-2 and PR-Q gene expression, which accelerated the defense response and reduced brown rot disease. The evaluated potato genotype results proved to have the potential for brown rot disease resistance and higher yield production. The findings of this study recommended that biopriming with a microbial consortium enhance potato growth, productivity, and induction of defense responses against S. tuberosum through the induction of systemic resistance via expression of PR pathogenic-related protein network. The present investigation offers significant perspectives that warrant further exploration in subsequent studies to address the traceability requirements of the worldwide economics of disease control for potato plants.